International Relations in Southeast Asia : The Struggle for Autonomy - Weatherbee, Donald E. (Lanham Rowman and Littlefield, 2015)
This balanced, comprehensive guide to Southeast Asian politics offers a sensible but nondogmatic realist approach to the region's international relations. In this revised, third edition, Donald E. Weatherbee lucidly explains the dynamics of the Southeast Asian subsystem as a struggle for autonomy in pursuit of national interests.
Include Index and Appendix
Keywords: Southeast Asia -- Diplomatic relations -- Politics and government